Electromagnetic interference impact of wireless power transfer system on data wireless channel - Baikova, Elena N. (2017)
Trabalho apresentado no 7th Advanced Doctoral Conference on Computing, Electrical and Industrial Systems, DoCEIS 2016, 11-13 abril 2016, Caparica, Portugal